Beyond Aesthetics in Wall Art: Graphic Mural, Source of Public Health Education on Malaria Parasite - Afolabi, Benjamin Eni-itan F.; Falusi, Tolulope Aduke; Adeloye, Abiodun Adebayo; Odewole, Peter Oluwagbenga (Universitas Ciputra, 2025)
Malaria remains a major public health challenge in Nigeria, contributing significantly to national morbidity and mortality rates. This study explores how graphic murals can function as a non-clinical approach to public health education, using creative visual design to raise awareness about malaria prevention and control. The research specifically investigates the relevance and impact of wall art as a visual communication tool among students of Olabisi Onabanjo University (OOU), Ibogun Campus. Anchored on the diffusion of innovation theory, the study applied a survey method supported by descriptive qualitative analysis to examine students’ frequency of malaria infection, perceptions of visual health communication, and responses to a designed educational mural. The findings revealed a high prevalence of malaria among students and insufficient institutional health interventions. The mural successfully served as an effective educational medium, improving students’ awareness of malaria parasites and prevention measures. These results suggest that graphic murals can serve as accessible, community-based platforms for health communication, extending beyond aesthetic purposes to influence behavior and promote wellbeing. The study recommends broader adoption of creative public health campaigns and institutional support for integrating art-based design strategies into health education initiatives.